1997
DOI: 10.1080/01688639708403850
|View full text |Cite
|
Sign up to set email alerts
|

Perseverations during paired-associate learning in Huntington's disease

Abstract: Verbal (word) and nonverbal (design) paired-associate tasks were administered to Huntington's disease (HD) patients and healthy control subjects. An AB-AC paradigm, in which the cue stimuli were paired with different responses on the learning (e.g., BED-REST) and test trials (e.g., BED-SHEET), was used. It was hypothesized that HD patients would continue to respond with AB associations on the AC trials. The results were contrary to expectations: Patients showed impaired learning of both verbal and nonverbal as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…One case report was excluded since the patient had no clinical signs or symptoms suggesting HD, DNA analysis was not available and he had a negative family history for HD [13]. One article did not use standardized or validated research instruments for OCBs or PBs, and was therefore excluded [14].…”
Section: Resultsmentioning
confidence: 99%
“…One case report was excluded since the patient had no clinical signs or symptoms suggesting HD, DNA analysis was not available and he had a negative family history for HD [13]. One article did not use standardized or validated research instruments for OCBs or PBs, and was therefore excluded [14].…”
Section: Resultsmentioning
confidence: 99%
“…Identification of location of different patterned objects that have been previously revealed and then occluded. Tests visual memory and learning (Rich et al, 1997).…”
Section: Paired Associates Learningmentioning
confidence: 99%
“…18 We identified that animals exposed to stroke exhibited robust deficits in two key metrics, namely the % of correct trials performed, which is considered to reference both learning and memory, as well as the number of repeated trials, which is considered to index perseveration. 18,32,33 Both the LOPC paradigms limited these deficits to a level that was comparable to that observed in sham animals. These findings align well with other studies that illustrate the effectiveness of LOPC to improve cognitive deficits after stroke.…”
Section: Discussionmentioning
confidence: 65%